A Modification of Laparoscopic Type C1 Hysterectomy to Reduce Postoperative Bladder Dysfunction: A Retrospective Study. Issue 3 (3rd April 2019) - Jiang, Wei; Liang, Meirong; Han, Douxing; Liu, Hui; Li, Ling; Zhong, Meiling; Luo, Lin; Zeng, Siyuan
ABSTRACT: Objective : To investigate the feasibility of a modified type C1 hysterectomy, using the deep uterine vein (DUV) and its branches as an anatomical landmark, to reduce postoperative bladder dysfunction in cervical cancer patients.Methods : One hundred fifty-two stage IA2–IIB cervical cancer patients were enrolled to undergo a laparoscopic hysterectomy. According to the operation methods, 93 or 59 of the patients were assigned to a type C1 hysterectomy (group 1), using the DUV and its branches as an anatomical landmark, and a type C2 hysterectomy (group 2), respectively. The baseline data, operation time, blood loss, hospitalization time, survival rate, and bladder dysfunction of both groups were compared.Results : The patients in group 1 experienced shorter overall and postoperative hospitalization time, less blood loss, and shorter catheterization time, as compared to those in group 2. There were no statistically significant differences in intraoperative damage, postoperative complications, numbers of dissected lymph nodes, and rates of positive resection margins between two groups. The incidences of long-term overall bladder dysfunction, urinary retention, and bladder-emptying difficulties were lower in group 1 than those in group 2. There was no statistically significant difference in bladder storage dysfunction, such as urinary incontinence and frequent urination, between two groups. The 3-year disease-free survival rates and 3-year overall survival rates in the two groups were both similar.Conclusion : Compared to type C2 hysterectomies, type C1 hysterectomies, using the DUV and its branches as an anatomical landmark, resulted in shorter hospitalization time, less blood loss, reduced bladder dysfunction, and uncompromised radicality.